Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11999-011-1964-1
|View full text |Cite
|
Sign up to set email alerts
|

All-Polyethylene Tibial Components in Obese Patients Are Associated With Low Failure at Midterm Followup

Abstract: Background In the United States, the obese population has increased markedly over the last four decades, and this trend continues. High patient weight places additional stress on TKA components, which may lead to increased polyethylene wear, osteolysis, radiolucencies, and clinical failure. Metalbacked tibial components and all-polyethylene tibial components in the general population have comparable osteolysis and failure, but it is unclear whether these components yield similar osteolysis and failure in obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(48 reference statements)
2
6
1
1
Order By: Relevance
“…An important finding of our study that strongly confirms previous observations [15][16][17][18][19][20][21][22][23][24][25][26][27] is that the outcome of total knee arthroplasty with all-polyethylene tibial components is better than those performed with metal-backed modular tibial designs. In our institution, all-polyethylene tibial components were used in 10% to 30% of the primary total knee arthroplasties each year, and PFC Sigma was the most commonly used brand (65%), followed by much smaller categories of other brands.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An important finding of our study that strongly confirms previous observations [15][16][17][18][19][20][21][22][23][24][25][26][27] is that the outcome of total knee arthroplasty with all-polyethylene tibial components is better than those performed with metal-backed modular tibial designs. In our institution, all-polyethylene tibial components were used in 10% to 30% of the primary total knee arthroplasties each year, and PFC Sigma was the most commonly used brand (65%), followed by much smaller categories of other brands.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, follow-up is limited with some of the more contemporary all-polyethylene tibial designs. Hence, we concur with other investigators 16,18,20,27 that the theoretical advantages of the metal-backing of the tibial component may not necessarily translate into clinical outcomes, and all-polyethylene designs can be successfully used in many patients with substantial cost savings.…”
Section: Discussionsupporting
confidence: 89%
“…We showed that none of the parameters for low-demand status (age, rheumatoid arthritis, weight) influenced the outcome of the comparison. Therefore, the all-polyethylene component could be an option for all patients with an indication for TKA as previously reported [12,31,36]. When there is a need for modular stems or augmentations, there is an indication for metal backing of the tibia since this cannot be added to the all-polyethylene tibial component.…”
Section: Discussionmentioning
confidence: 93%
“…The all-polyethylene tibial component is less expensive than its modular counterpart 6 , and several randomized trials and smaller cohort studies have indicated that the allpolyethylene tibial component is at least equivalent to the modular design in function, knee motion, primary stability, and long-term implant survival [7][8][9][10][11][12] . These favorable findings also apply to patients with rheumatoid arthritis or obesity 13,14 . A recent meta-analysis concluded that ''the AP [all-polyethylene] tibial component was comparable with or better than the MB [metal-backed] tibial component in TKA [total knee arthroplasty].''…”
mentioning
confidence: 73%